2021
DOI: 10.2172/1818842
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Wind Market Report: 2021 Edition

Abstract: The Offshore Wind Market Report: 2024 Edition provides detailed information on the U.S. and global offshore wind energy industries to inform policymakers, researchers, and analysts about technology, economic, and market trends. The report provides the status of more than 322 operating offshore wind energy projects in the global fleet through Dec. 31, 2023, as well as the broader global pipeline of projects in various development stages. To provide current information and discussion on the emerging offshore win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…This result is not surprising because the underlying data-both the cost rates in ORBIT, which are used to establish the baseline results, and the learning rates derived from historic project data-are based on insights from the European market. The North America fixed-bottom costs from Wiser et al (2021) are higher than those predicted by the FORCE model, which could reflect uncertainty about the growth of a new domestic industry; however, recent power offtake agreements in the United States have suggested that these projects can be cost-competitive (or, in some cases, cheaper than) European projects (Musial et al 2021;Beiter et al 2021a). As such, it is encouraging that the FORCE forecast aligns with the expert predictions for the European market.…”
Section: Projected Capital Costsmentioning
confidence: 94%
See 2 more Smart Citations
“…This result is not surprising because the underlying data-both the cost rates in ORBIT, which are used to establish the baseline results, and the learning rates derived from historic project data-are based on insights from the European market. The North America fixed-bottom costs from Wiser et al (2021) are higher than those predicted by the FORCE model, which could reflect uncertainty about the growth of a new domestic industry; however, recent power offtake agreements in the United States have suggested that these projects can be cost-competitive (or, in some cases, cheaper than) European projects (Musial et al 2021;Beiter et al 2021a). As such, it is encouraging that the FORCE forecast aligns with the expert predictions for the European market.…”
Section: Projected Capital Costsmentioning
confidence: 94%
“…The rate of decrease in CapEx depends on the deployment rate of fixed-bottom and floating wind. We used the fixedbottom deployment rate through 2035 from Musial et al (2021), which leads to a total global deployment of 276 GW at the end of 2035. We linearized this deployment projection to provide a smoother CapEx trajectory.…”
Section: Project Average Capex Into the Futurementioning
confidence: 99%
See 1 more Smart Citation
“…A growing international focus on the "blue economy" represents a changing industrial landscape for our seas, which is exemplified by the rapid growth of offshore wind throughout the world (Global Wind Energy Council, 2020;Musial et al, 2021). Forecasting of ocean wave conditions is a fundamental requirement for the operation and maintenance of offshore and coastal infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…At these levels for ongoing wind deployment, decarbonization targets will likely not be achieved. Yet, land-based and offshore wind can potentially be deployed at even greater scale throughout the United States, especially as the technology progresses (Wiser et al 2021;Musial et al 2021), making it a key player in transforming the energy sector.…”
Section: Introductionmentioning
confidence: 99%